An automated motivational interview promotes donation intention and self‐efficacy among experienced whole blood donors. Issue 9 (14th June 2019) - Livitz, Irina E.; France, Christopher R.; France, Janis L.; Fox, Kristen R.; Ankawi, Brett; Slepian, P. Maxwell; Kessler, Debra A.; Rebosa, Mark; Shaz, Beth H.
Abstract : BACKGROUND: Interventions intended to motivate donors to return can be costly and time consuming. The current study examined the effect of a Web‐based automated interview, informed by motivational interviewing and self‐determination theory, on donor intention, motivation, and behavior in a sample of highly experienced donors. STUDY DESIGN AND METHODS: Approximately 1 week after donating, 1177 highly experienced whole blood donors (mean prior donations, 35.5; mean age, 46.9 years; 66.3% female) participated in a study in which they were randomly assigned to either a donor motivational interview (n = 544) or knowledge interview (n = 633). Measures of donor motivation and psychological need support were obtained before the interviews, and again at postinterview assessments conducted approximately 2 days later and 7 weeks later. Blood center records were used to assess repeat donation attempts for 1 year after the interviews. RESULTS: Relative to the knowledge interview, participants in the motivational interview had larger increases in donation intention and self‐efficacy from preinterview to the first follow‐up. Among women only, the motivational interview was associated with greater competence and relatedness increases at both follow‐up assessments. CONCLUSION: An automated motivational interview appears to be a feasible way to promote donation intention and self‐efficacy. Although the observed effects were small among highly experienced donors, we are currently assessing the potential effect of this intervention among less experienced donors.